2010
DOI: 10.1039/c0cc03600e
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous immunization by a solid-in-oil nanodispersion

Abstract: We have successfully achieved transcutaneous immunization without the use of any skin pre-treatment or immune-stimulant adjuvant by applying a solid-in-oil (S/O) nanodispersion: an oil-based nanodispersion of antigens coated with hydrophobic surfactant molecules. This finding indicates that the S/O nanodispersion has great promise for effective transcutaneous vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 25 publications
0
30
0
2
Order By: Relevance
“…Consequently, 7crpR had a higher affinity for sucrose laurate which hydrophile-lipophile balance value is 1. Our previous investigations demonstrated a mechanism of protein permeation through the S/O nanodispersion system: surfactant molecules were removed in the outermost SC layer and hydrophilic molecules only permeate into the hydrophilic layers in skin (20). Thus, inefficient removal of surfactant depressed the permeation of 7crpR into epidermis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, 7crpR had a higher affinity for sucrose laurate which hydrophile-lipophile balance value is 1. Our previous investigations demonstrated a mechanism of protein permeation through the S/O nanodispersion system: surfactant molecules were removed in the outermost SC layer and hydrophilic molecules only permeate into the hydrophilic layers in skin (20). Thus, inefficient removal of surfactant depressed the permeation of 7crpR into epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…A S/O nanodispersion was prepared as previously reported (20). A 2.0-mL 7crpR aqueous solution (0.5 mg/mL) and a 4.0-mL L-195 cyclohexane solution (12.5 mg/mL) were homogenized with a polytron homogenizer (Kinematica AG, Luzern, Switzerland) at 26,000 rpm for 2 min to obtain a water-in-oil (W/O) emulsion.…”
Section: Preparation Of S/o Nanodispersions Containing 7crprmentioning
confidence: 99%
See 2 more Smart Citations
“…The complex was easily dispersed into the oil to obtain a homogeneous and transparent oil-based protein dispersion, without loss of yield. According to previous studies, proteins cannot be dispersed as physical mixtures in oil, even in the presence of surfactant, and generally proteins precipitate in oil (Tahara et al, 2010, described this as a physical mixture). This indicated that the W/O emulsionmediated process played an important role in coating proteins with surfactants so that proteins would not precipitate.…”
Section: A Novel Methods To Produce Surfactant-protein Complexesmentioning
confidence: 98%